PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF DIGITAL PADA TEMA 2 DI KELAS VI - Siti Hamidah Hamidah; Asep Samsudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to test whether there are increase in the ability to understand the concept of multipication between student who learn to use the Realistic Mathematics Education (RME) model and students who not to learn use the Realistic Mathematics Education (RME) model. The method chosen is mix methods and the type of research is in the form of sequential explanatory, which aims for researcher to obtain quantitative data first and followed by an explanation of qualitative data. The increase in concept understanding ability can be seen from the increase in test results from 55.6% to 73.6. And from qualitative data obtained that the difficulty of students is difficult to memorize multiplication. While the difficulty of the teacher is difficult to condition the class and difficult to find appropriate props.